The Mediating Role of Parenting: How parental well-being and distress influence child behaviors - Sumargi, Agnes Maria; Prasetyo, Eli (Universitas Ahmad Dahlan, 2024)
Children’s problem behaviors should be managed properly while their prosocial behaviors should be nurtured. As parents play a significant role in children’s lives, their well-being and psychological distress could influence children’s behavior through different mechanisms. This study investigated the roles of effective parenting (positive encouragement and parent-child relationship) and ineffective parenting (parental inconsistency and coercive parenting) in mediating the relationships between parental well-being and psychological distress, and children’s problem and prosocial behavior as reported by parents. One-hundred and seventy-three parents of primary school children completed a paper and pencil survey consisting relevant measures. Mediation analyses using PROCESS macros showed that parental well-being and psychological distress significantly influenced children’s problem behavior through effective and ineffective parenting, respectively. However, only parental well-being significantly influenced children’s prosocial behavior through effective parenting. The results highlight the importance of parental well-being, as it fosters positive parenting practices and promotes prosocial behavior in children. Keywords: child problem behaviors, child prosocial behaviors, parenting, psychological distress, parental well-being.